Innovations in virtual and augmented reality: Transforming organizational culture management for the 21st century - Brito, Elizângela de Macêdo; Arruda, Ângela Maria de; Brandim, Ayrton de Sá; Sebaio, Amanda Gabriele; Pereira, Becholina Aline; Santos, Eduardo Igor da Silva; Caixeta, Higor Gonçalves; Nascimento, Jordão Pereira do; Lemos, Ludmila de Fátima; Pereira, Marcos Vinícius (Seven Editora, 2024)
The application of Augmented Reality (AR) and Virtual Reality (VR) in management and organiza-tional culture is emerging as an innovative strategy to increase efficiency, collaboration and emplo-yee engagement. This study aimed to investigate the impact of these technologies on organizational management, highlighting the benefits, challenges and best practices for their implementation. The justification is based on evidence that AR and VR can significantly improve knowledge retention and employee productivity, as demonstrated in studies by PwC (2020) and Deloitte (2021). As a me-thodology, a mixed approach was adopted, combining qualitative and quantitative methods. In the qualitative phase, semi-structured interviews were carried out with managers and experts from com-panies that use AR and VR, revealing topics such as improving the integration of new employees and increasing operational efficiency. In the quantitative phase, a questionnaire was applied to 233 employees, evaluating satisfaction, engagement and productivity after implementing these techno-logies. The results indicate that 78% of employees reported greater job satisfaction, and 82% felt more engaged and motivated. Additionally, 65% of participants saw an increase in productivity. Sta-tistical analysis revealed significant correlations between the use of AR/VR and improvements in organizational performance indicators, with linear regression explaining 48% of the variation in pro-ductivity (R² = 0.48, p < 0.01) and ANOVA showing significant differences in job satisfaction. work (F = 7.62, p < 0.01). In conclusion, it was found that the integration of AR and VR in organizational management provides a series of benefits, including greater efficiency and employee engagement. However, successful implementation requires strategic investments in infrastructure and ongoing training to overcome initial challenges and maximize long-term benefits. DOI:https://doi.org/10.56238/sevened2024.010-047